Inadvertent intralenticular dexamethasone implant: 1-year follow-up and management - Caglar, Cagatay (Oman J Ophthalmol, 2017)
We report the case of a 72-year-old female who developed macular edema (ME) due to hemicentral retinal vein occlusion in her right eye. A dexamethasone implant was inadvertently injected into the crystalline lens. The patient was followed without repositioning of the dexamethasone implant during the 12 months. Besides, the posterior subcapsular cataract and ME had progressed significantly; hence, cataract extraction and intravitreal ranibizumab injection were performed in the same session. A three-piece intraocular lens was implanted in the sulcus with optic captured, and then intravitreal ranibizumab injection was performed. The patient had an uncomplicated postoperative recovery. At 2 months, best-corrected visual acuity was 0.7, and the macula was dry.